The Impact of Nutrition Education in Workplace - Salim, Agus; Basrowi, Ray Wagiu (Journal of Indonesian Specialized Nutrition, 2024)
Workplace is one of the places that could affect wide range of health, functioning, and quality-of-life outcomes and risks. this study aims to review nutrition education among workers that result can be used as the evidence based for policymakers to start implementing health and nutrition education periodically. We conducted a search on the PubMed Central database in May 2024 to look at various publications and journals in 2010-2024 related to the nutritional education in the workplace using the keywords: nutrition education, workplace. Three studies were meet inclusion and exclusion criteria and further be reviewed. Three studies focused on nutrition education in the workplace. Positive outcomes were recorded for all workplace intervention, including increase in nutrition knowledge, self-efficacy, reduce risky behavior, and improved body mass index and blood biomarkers. Workplace may provide an optimal setting to reach a large proportion of the adult population thus could improve both nutrition education and practice as well as health status. Workplace education related to nutrition, in this paper all gives different positive outcomes